Impacts of Methyl Farnesoate and 20-Hydroxyecdysone on Larval Mortality and Metamorphosis in the Kuruma Prawn Marsupenaeus japonicus - Toyota, Kenji; Yamane, Fumihiro; Ohira, Tsuyoshi (Frontiers in Endocrinology, 2020)
Physiological functions of juvenile hormone (JH) and molting hormone have been demonstrated in insects. JH, molting hormone and their mimics (insect growth regulators, IGRs) show endocrine-disrupting effects not only on target pest insects but also on other arthropod species such as crustaceans. However, little is known about the endocrine-disrupting effects of IGRs on benthic crustaceans. In this study, laboratory experiments were conducted to investigate effects of representative innate JH in crustaceans (methyl farnesoate, MF) and molting hormone (20-hydroxyecdysone, 20E, active form of ecdysteroid) on larval stages of the kuruma prawn Marsupenaeus japonicus, which is a decapod crustacean living in warm seawater. Larval development of kuruma prawn progresses in the order of nauplius, zoea, mysis, and then post-larvae with molting and metamorphosis, but it is unknown whether both MF and 20E have crucial roles in metamorphosis and molting of this species. Treatments of either MF or 20E on shrimp larvae were attempted at each developmental stage and those effects were validated. In terms of EC50 values between mortality and metamorphosis, there were apparent differences in the transition from nauplius to zoea (MF: 7.67 and 0.12 μM; 20E: 3.84 and 0.06 μM in survival and metamorphic rates, respectively). In contrast, EC50 values in MF and 20E treatments showed high consistency in the transitions between zoea to mysis (EC50 values for survival; MF: 1.25 and 20E: 0.22 μM), and mysis to post-larvae (EC50 values for survival; MF: 0.65 and 20E: 0.46 μM). These data suggest that nauplius has strong resistance against exposure to MF and 20E. Moreover, both chemicals induced high mortality triggered by the disruption of molting associated with metamorphosis. To our knowledge, this is the first experimental evidence that investigates in vivo physiological functions of MF and 20E in the larval stages of kuruma prawn, shedding light on not only ecotoxicological impacts of IGRs released into nature, but also endocrine mechanisms underlying larval development with metamorphosis in benthic decapod crustaceans.